Clinical utility of capsule endoscopy in small intestinal diseases, experience of single referral center with 125 cases - Kav, Taylan; Shorbagi, Ali I.; Sivri, Bulent; Balaban, Yasemin H.; Arslan, Serap; Batman, Figen; Bayraktar, Yusuf (Gastroenterology Review/Przegląd Gastroenterologiczny, 2009)
Aim: To evaluate the clinical utility of capsule endoscopy in diagnosing small bowel disease. Material and methods: A retrospective review of 125 capsule endoscopy (CE) examinations from September 2003 to March 2009 was performed. Results: The average patient age was 47.7 ±18.2 (min: 13, max: 97), 49 were female (39.2%). Indications for CE were obscure gastrointestinal bleeding (OGIB) (56.0% of cases), diarrhea (14.0%), abdominal pain (7.2%), other indications such as known Crohn’s disease, and surveillance for polyposis syndromes. The CE completely evaluated the entire small bowel in 92 patients (73.6%). Capsule endoscopy study was normal without any finding in 22.4% of patients. The overall diagnostic yield of capsule endoscopy was 74.4% (93/125). The diagnostic yield of obscure gastrointestinal bleeding by capsule endoscopy was 77.1%. No complication related to the capsule was observed. Conclusions: Capsule endoscopy is safe and well tolerated diagnostic tool in the evaluation of small bowel diseases.